2018
DOI: 10.1007/s12298-018-0599-z
|View full text |Cite
|
Sign up to set email alerts
|

Studies on root anatomy, morphology and physiology of rice grown under aerobic and anaerobic conditions

Abstract: With the changing climate and rainfall abrasions, there is a gradual shift in the system of rice cultivation from traditional transplanted anaerobic to aerobic system. Studies on the root anatomical and morpho-physiological traits provide insights about the adaptation under aerobic conditions. We investigated the root anatomical and morpho-physiological traits in anaerobic (BPT 5204) and aerobic (CR Dhan 202) adapted rice genotypes grown under anaerobic and aerobic conditions. It was observed that the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
2
10
0
1
Order By: Relevance
“…It was shown that the deeper root system and the root penetration ability guarantee the acquisition of water and nutrients for the plant [ 8 , 38 , 39 ], and thus the very shallow and narrow root system is effectively decreasing the soil exploration rate [ 18 ]. The effect of the increase in the medium strength and the decrease in the hydraulic properties on the root penetration rate of cedar seedlings was found to be strong (Tables 1 and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the deeper root system and the root penetration ability guarantee the acquisition of water and nutrients for the plant [ 8 , 38 , 39 ], and thus the very shallow and narrow root system is effectively decreasing the soil exploration rate [ 18 ]. The effect of the increase in the medium strength and the decrease in the hydraulic properties on the root penetration rate of cedar seedlings was found to be strong (Tables 1 and 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…A relevant correlation between the RL and the LMXN could not be observed, most likely due to the impossibility of harvesting the root as a whole under eld conditions. However, several reports noted that water-conducting tissue tend to be smaller, plants tend to develop more LMXN to compensate smaller diameters 48,50,51 . Narrow xylem diameter, particularly in seminal roots, was reported to optimize soil water from deep soil pro le for plant utility, especially during maturation 50 , whereas broad xylem diameter in deep-growing roots were known to also improve the exploration of available water within deep soil horizons 4,52 .…”
Section: Discussionmentioning
confidence: 99%
“…As OCS lines already tend to produce longer RL, a thick cortical area would extend their tness disadvantages in terms of energy allocations away from the seeds 54 . Moreover, aerenchyma (air cavities that consist of gas-lled spaces) plays a vital role in the long-distance transport of oxygen from the shoots to the root tips which is particularly important in the adaptability and survival of plants particularly under stressful growing condition 51 . Root aerenchyma has been related to improving crop growth in maize plants grown under water-de cit conditions 52,55 .…”
Section: Discussionmentioning
confidence: 99%
“…Akar berperan penting dalam menyerap hara dan menyimpan asimilatnya serta mengembangkannya menjadi jaringan baru. Morfofisiologis akar berbeda-beda terutama jika dalam fase hidupnya mengalami cekaman biotik maupun abiotik (Phule et al 2019;Karlova et al 2021).…”
Section: Bobot Kering Akarunclassified